PENGARUH TATA KELOLA PERUSAHAAN TERHADAP PROFITABILITAS (ROA) (Studi Perbandingan Antara Bank Umum Syariah dan Bank Umum Konvensional 2019-2023): THE EFFECT OF COMPANY GOVERNANCE ON PROFITABILITY (ROA) (Comparative Study Between Islamic Commercial Banks and Conventional Commercial Banks 2019-2023) - Tresna Pancha Desyana; Taufik Hidayat; Rizky Maulana Putra (An Nuqud Journal of Islamic Economics, 2025)
Good corporate governance plays an important role in increasing the profitability of a financial institution, especially through the supervisory mechanism by the independent board of commissioners and the strategic policies implemented by the board of directors. The main focus of the research is to analyze the effect of corporate governance on profitability (ROA) with a comparative study between Islamic commercial banks and conventional commercial banks in the 2019-2023 period. This study uses a quantitative approach with multiple linear regression methods and the form of data used is panel data. The results showed that simultaneously the independent board of commissioners and the board of directors had a significant influence on profitability (ROA) in Islamic commercial banks and conventional commercial banks. Partially, the independent board of commissioners and the board of directors at Islamic commercial banks have a significant influence on profitability (ROA). While in conventional commercial banks, only the board of directors has a significant effect on profitability (ROA), while the independent board of commissioners does not have a significant impact. These findings indicate that corporate governance contributes to profitability, with different patterns of influence between the two types of banks. Keywords: independent board of commissioners, board of directors, ROA